Sebuah Eksplorasi Optimisme Wanita Infertil Ditinjau dari Koping Religius Positif dan Komunikasi Pasangan - Ulfaviani Laksita Anisa; Berliana Widi Scarvanovi; Istar Yuliadi; Indah Kusumaningrum (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
Stress in infertile women may negatively affect their treatment outcomes. Therefore, fostering positive feelings such as optimism during treatment is crucial. Optimism can be achieved by having an adaptive coping strategy and maintaining quality communication between partners. This research is intended to determine the correlation between positive religious coping and marital communication quality with optimism in infertile women. This research used a quantitative approach with research instruments consisting of an optimism scale, a positive religious coping scale, and a marital communication quality scale. The sample consisted of 50 infertile women in the fertility clinic of a hospital in Surakarta, Indonesia. The study found that positive religious coping and the quality of marital communication simultaneously predict optimism among infertile women (p = 0,000), accounting for 37,8% of the variance. Furthermore, partial analysis indicated that without marital communication quality, optimism and positive religious coping are not significantly correlated (p = 0,103). Conversely, without positive religious coping, marital communication quality remains significantly related to optimism (p = 0,032). This means that women seeking infertility treatment view their partner’s support as an essential factor in fostering optimism during the treatment process.